PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KERJA SAMA PEGAWAI DI KANTOR KECAMATAN TAKA BONERATE KABUPATEN KEPULAUAN SELAYAR - Ati, Rayu; Malik, Ihyani; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2022)
ABSTRACT This study aimed to find out the effect of non-physical work environment variables on employee cooperation variables at the Taka Bonerate District Office, Selayar Islands Regency. The method used in this study was a quantitative research method, the research data were analyzed using descriptive statistics with a simple linear regression formula. The data collection technique used questionnaire and strengthened by the results of observations/field observations and documentation studies. In this study, the sampling technique was saturated random sampling. Looking at the number of populations that were less than 100 people,the entire population was used as a sample, which was as many as 30 people. The results showed, based on the output of the summary model, the results obtained were R/standardized Cofficients Beta of 0.324 or 32,4%. That was, the calculation showed that there was a positive and significant influence between the non-physical work environment on employee cooperation at the Taka Bonerate District Office, Selayar Island Regency. Keywords: Non-physical Work Environment, Cooperation